THE CONCENTRATION OF THE AGRICULTURE AND LIVESTOCK SECTOR IN THE VISEGRAD GROUP AFTER MEMBERSHIP TO THE EUROPEAN UNION - Bozduman, Elif Tuğçe (Economics of Agriculture, 2023)
In the study, after the European Union (EU) membership of the Visegrad group (since 2004), both export and import levels were analyzed in products representing the agriculture and livestock sector. The results of the analysis show us that. The fact that the Visegrad group has EU membership has reduced the level of concentration over time. CR and HHI, the two most commonly used concentration analyses in the literature, were used as methods. Among the Visegrad countries, the country with the highest concentration of exports in agricultural and livestock products is Hungary and the country with the lowest is Poland. On the contrary, the country with the highest concentration of imports is Poland and the country with the lowest concentration is Hungary.